Factors Causing Primary Infertility In Couples Of Reproductive Age: Literature Review - Wahyuni, Eko Sari; Setyarini, Anggun (Health Access Journal, 2024)
Primary infertility, the inability of couples of reproduvtive age to conceive after 12 months of unprotected sexual intercourse, is a complex health problem with multiple causative factors. This literature review aims to identify and analyze factors associated with primary infertility in couples of reproductive age. The search method was conducted on electronic databases such as PubMed, ScienceDirect, and Google Scholar with the keywords “primary infertility”, “infertility factors”, “reproductive age couples”, and “literature review”. The results of the literature review found that primary infertility can be caused by various factors, both from the man (sperm quality disorders, sexual function, reproductive tract infections, chromosomal abnormalities, varicocele, lifestyle), woman (ovulation disorders, fallopian tubes, endometriosis, uterus, hormonal, lifestyle), and partner (age, lifestyle, environment, stress). These factors can be interrelated and result in primary infertility. It can be concluded that primary infertility is a complex and multifactorial health issue. Understanding these factors is important to help couples achieve pregnancy and improve their quality of life.